Pathology implications for the physical therapist - Goodman, Catherine Cavallaro MBA, PT, CBP; Fuller, Kenda S. PT
The new fourth edition of this only pathology book written specifically for physical therapists includes the latest information on the pathogenesis of musculoskeletal and neuromuscular disorders and other medical conditions, as well as their medical diagnosis and treatment, and most importantly, the special implications for the therapist